Religiosity and Effortful Control as Predictors of Indonesian Adolescents' Tobacco and Alcohol Use: Moderation and Mediation. (17th June 2019) - French, Doran C.; Purwono, Urip; Zhao, Siman; Shen, Mengqian; Eisenberg, Nancy
Abstract : Moderation and mediation models of religiosity and effortful control as predictors of tobacco and alcohol use were tested in this 2‐year longitudinal study of 563 16‐year‐old Muslim Indonesian adolescents. Adolescents reported their effortful control, religiosity, and tobacco and alcohol use and peers provided reports of adolescents' effortful control. Although both moderation and mediation effects emerged when predicting Year 2 substance use, predictions of change from Year 1 to Year 2 substance use yielded effects of moderation for peer‐ but not self‐reported effortful control for boys; no mediation effects emerged. These findings provide evidence of interconnections between effortful control and religiosity as predictors of substance use and suggest the need for further longitudinal studies that compare moderation and mediation models.